2022
DOI: 10.31083/j.fbl2702071
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin B exerts neuroprotection in a murine Alzheimer’s disease model by modulating oxidative stress, inflammation, and neurotransmitter levels

Abstract: Background: Alzheimer's disease (AD) type dementia encompasses diverse cognitive deficits marked by free radicals and proinflammatory cytokines mediated progressive neurodegeneration and vascular damage including the blood-brain barrier. Subsequently, an imbalance in neurotransmitters, excitotoxicity, and synaptic loss provide impetus to AD pathogenesis and perpetuate brain dysfunctions. Cucurbitacin possesses several biological properties and has shown potential in cancer, diabetes, and brain disorders. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…Intracerebroventricular injection of STZ induces pathological changes at molecular, cellular, and behavioral levels—similar to those observed in the sporadic form of AD ( Salkovic-Petrisic et al, 2013 ; Grieb, 2016 ). Upon central application, STZ generates central insulin resistance resulting in glucose hypometabolism, mitochondrial damage, and the generation of intracellular oxidative and nitrosative stress ( Liu et al, 2022 ). It has been demonstrated that STZ promotes oxidative/nitrosative stress in rat brains detected as early as 1 week post-application and was present even 8 weeks following the acute application, suggesting ongoing degenerative processes ( Sharma and Gupta, 2001 ; Ishrat et al, 2006 ; Pathan et al, 2006 ; Shoham et al, 2007 ; Saxena et al, 2011 ; Alluri et al, 2020 ; Akhtar et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracerebroventricular injection of STZ induces pathological changes at molecular, cellular, and behavioral levels—similar to those observed in the sporadic form of AD ( Salkovic-Petrisic et al, 2013 ; Grieb, 2016 ). Upon central application, STZ generates central insulin resistance resulting in glucose hypometabolism, mitochondrial damage, and the generation of intracellular oxidative and nitrosative stress ( Liu et al, 2022 ). It has been demonstrated that STZ promotes oxidative/nitrosative stress in rat brains detected as early as 1 week post-application and was present even 8 weeks following the acute application, suggesting ongoing degenerative processes ( Sharma and Gupta, 2001 ; Ishrat et al, 2006 ; Pathan et al, 2006 ; Shoham et al, 2007 ; Saxena et al, 2011 ; Alluri et al, 2020 ; Akhtar et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results confirm that icv STZ induces chronic degenerative changes coupled with oxidative imbalance, not only in the structures related to learning and memory processes, but in virtually all examined brain regions. It has been shown that STZ-induced oxidative stress can directly trigger lipid peroxidation resulting in increased levels of MDA ( Farbood et al, 2020 ), as well as the change in the methylation pattern of DNA, leading to a cascade of neurodegenerative events marked by an increased 8OHdG level ( Liu et al, 2022 ). On the other hand, antioxidative mechanisms have been shown to be significantly impaired in STZ-administrated rats, mostly noted in the cortex and hippocampus region ( Alluri et al, 2020 ; Bavarsad et al, 2020 ; Akhtar et al, 2021 ; Liang et al, 2021 ; Tiwari et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our in vivo observations were also confirmed by postmortem assessment of oxidative stress and an overall increase of lipid peroxidation was observed in AD-T2D animals, when compared with AD alone. It should be noted that oxidative stress alters lipid-lipid interaction leading to impaired membrane permeability [ 76 ] and high levels of markers of oxidative stress-induced lipid peroxidation and cytotoxicity such as 4-hydroxynonenal, MDA or thiobarbituric acid reactive substances are increased in AD [ 77 , 78 ] and diabetes [ 79 , 80 ] supporting a synergistic effect when both diseases coexist. In addition, lipid peroxidation is accompanied by structural and functional alterations of the microvasculature [ 69 ], that may ultimately contribute to the observed pathology when AD and T2D coexist.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning cucurbitacins, their chemoprotective and antioxidant capacity has been shown [44][45][46]. Specifically, cucurbitacins I, D, B, and E can promote the expression of heme oxygenase-1 (HO-1) and NAD(P)H dehydrogenase quinone 1 (NQO-1), which are phase II detoxification enzymes; the mechanisms proposed implies the regulation of the Nrf2 transcription factor, which in turn modulates the expression of SOD, GPx, and CAT.…”
Section: Discussionmentioning
confidence: 99%